The Effect of Scapular Stabilization Exercises on Alignment, Joint Position Sense, and Functional Stability of the Upper Limbs in Adolescent Girls with Upper Crossed Syndrome: A Randomized Controlled Trial - Maryam Nemati; Farzaneh Saki; Farzaneh Ramezani (Shiraz University of Medical Sciences, 2024)
Background: Upper crossed syndrome (UCS) is a prevalent postural issue among adolescents, with a rapid increase in its occurrence. This study aimed to investigate the impact of scapular stabilization exercises on alignment, joint position sense, and functional stability of the upper limbs in adolescent girls with UCS.Methods: This randomized, controlled trial, double-blind study was conducted in December 2022 at the Laboratory of Sport Science of Bu-Ali Sina University, Hamedan, Iran. The study included 48 adolescent girls with UCS. The participants were randomly assigned into either the experimental or the control group. The experimental group performed scapular stabilization exercises for eight weeks and the control group received no intervention. The outcome measures were kyphosis angle measured by a flexible ruler, forward head and rounded shoulder angles measured by photography and Kinovea software, shoulder joint position sense measured by a goniometer, and upper limb functional stability measured by the upper quarter Y-balance test. The assessments were done before and after the intervention.Results: The results showed that the experimental group improved significantly more than the control group on all the outcome measures (P<0.05). The experimental group had a significant decrease in kyphosis (P=0.001, 95%CI=[3.05%, 7.27%]), forward head (P=0.001, 95%CI=[4.21%, 7.70%]), rounded shoulder (P=0.001, 95%CI=[5.01%, 8.40%]) angles, and in joint reposition error (P=0.001, 95%CI=[1.07%, 2.89%]). Also, there was a significant improvement in upper limb functional stability in the right (P=0.042, 95%CI=[-3.56%, -0.91%]) and left (P=0.032, 95%CI=[-4.31%, -0.20%]) directions, as compared with the control group.Conclusion: The study results indicated that scapular stabilization exercises can improve alignment, joint position sense, and functional stability of the upper limbs in adolescent girls with UCS. Therefore, these exercises could be an effective intervention for preventing or treating UCS and its associated problems.